SOURCES RELATED TO THE HISTORY OF THE IRRIGATION CONSTRUCTION OF THE KASHKADARYA OAZIS - Jabbarova Ikbol Khujamuratovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The article studies and analyzes the works created on the history of the formation of culture, related to the development of new lands, the construction of irrigation facilities, the creation of agricultural oases in the Kashkadarya oasis.